PENGGUNAAN GRUP WHATSAPP BAGI MAHASISWA SEBAGAI MEDIA DAKWAH - Melsa Tri Wulandari; Jaelani Jaelani; Manja Manja (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2021)
WhatsApp (WA) is one of the popular communication media that serves to establish easy communication between users. The use of available WA groups can also be used as a medium of da'wah. Even so, the use of media also has a negative impact if it is not used wisely. Vice versa, if used with a good purpose, it will have a positive impact on its users. The purpose of this research in general is to find out the form of using WA groups and the materials used, as well as to determine the impact of using WA groups as a medium of da'wah for PAUD study program students class 2018. This study uses a communication approach with qualitative research types and is based on Harold's communication theory. Lasswell. Data collection techniques are carried out by observation, interviews, documentation. Data analysis techniques were taken through data reduction, data presentation, and verification/drawing conclusions and using data triangulation techniques as a method of data validity. The results showed that, 1) The form of using WA groups as a medium of da'wah such as the presence of users sharing information about Islamic studies, sharing updated information and discussions between other users. 2) The da'wah materials that are shared are quite complete, some contain aqidah, sharia, morals, and muamalah. 3) The impact felt by users is that it makes it easier for users to do good and establish friendship with other members so as to form good student character/morals.